1998
DOI: 10.1021/jm980452a
|View full text |Cite
|
Sign up to set email alerts
|

Spiperone:  Influence of Spiro Ring Substituents on 5-HT2ASerotonin Receptor Binding

Abstract: Spiperone (1) is a widely used pharmacological tool that acts as a potent dopamine D2, serotonin 5-HT1A, and serotonin 5-HT2A antagonist. Although spiperone also binds at 5-HT2C receptors, it is one of the very few agents that display some (ca. 1000-fold) binding selectivity for 5-HT2A versus 5-HT2C receptors and, hence, might serve as a useful template for the development of novel 5-HT2A antagonists if the impact of its various substituent groups on binding was known. In the present investigation we focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…The first region of the spiro ring to be addressed was the N 1 -phenyl substituent [20]. Interestingly, the N 1 -cyclohexyl derivative 45 (Table 5) had a binding profile similar to that of spiperone.…”
Section: Ether Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first region of the spiro ring to be addressed was the N 1 -phenyl substituent [20]. Interestingly, the N 1 -cyclohexyl derivative 45 (Table 5) had a binding profile similar to that of spiperone.…”
Section: Ether Analogsmentioning
confidence: 99%
“…It appeared that a substituent smaller than isopropyl but larger than -H was necessary. The smaller N 1 -alkyl derivatives (i.e., methyl, ethyl) were examined and the N 1 -methyl compound 48 (KML-010) was identified as a reasonable compromise [20]. Although 48 binds at 5-HT 2A receptors with 10-fold lower affinity than spiperone, it lacks affinity for 5-HT 2C and 5-HT 1A receptors, and its affinity for D2 dopamine receptors is 400-fold lower than that of spiperone.…”
Section: Ether Analogsmentioning
confidence: 99%
“…1982;Kovacs and de Wied 1978;Seliger 1975;Seliger 1977). Remoxipride (3-10 mol/kg) produced a decrease in general motor activity and a profound increase in training latencies without any effect on PA retention; whereas, raclopride affected neither PA training nor retention performance.Unlike remoxipride and raclopride, spiperone (two times higher affinity for DA D 2 receptors than for the 5-HT 2A receptors) (Leysen et al 1993;Metwally et al 1998) produced an impairment of PA retention at the 0.1 mg/ kg dose, which is at the threshold for induction of catalepsy (Hess et al 1988). Interestingly, the doses of spiperone (0.03 mg/kg IP), remoxipride (3 mol/kg SC), and raclopride (0.1-0.3 mol/kg IP) used in the combination studies with PCA or 8-OH-DPAT have been reported to block DA agonist-induced hyperactivity (Magnusson et al 1986;Ögren 1996;Ögren and Archer 1994;Ögren et al 1990;, thus indicating DA (predominantly, D 2 ) receptor antagonism in vivo, albeit devoid of apparent catalepsy.…”
mentioning
confidence: 99%
“…Pyrrolidine, 1-3 isoxazoline [4][5][6] and piperidine [7][8][9] substructures exhibit important biological activities. The 1,3-dipolar cycloaddition of nitrile oxides to azomethine ylide to alkenes affords pyrrolidines and isoxazolines.…”
Section: Introductionmentioning
confidence: 99%